A Comparative Study on Factors Influencing Chinese and Indonesian Students to Study in Malaysia’s Private Higher Learning Institutions - Antalius, Samuel (2010)
This study is carried out with the aim to propose recommendations to Malaysia government as well as private institution of higher learning to promote the education industry in Malaysia since international students are decreasing especially Chinese and Indonesians students. By identifying the factors that influence Indonesian and Chinese students to study in Malaysia, the results of this research offer information for local government and private institutions of higher learning to develop positioning and marketing communication strategies to attract Indonesian and Chinese students for Sichuan. The identification of factors such as “Push” and “Pull” factors influence international students from China and Indonesia to study in Malaysia. The most contribution of this research is the result on the similarities and differences between the factors influencing Indonesian and Chinese students to study in Malaysia where there is limited research done in this particular area.